INTELLECTUAL CAPITAL: STRATEGIC PERSPECTIVE OF UNIVERSITY IN A KNOWLEDGE MANAGEMENT MODEL AND ITS APPLICATION IN THE FORMATION OF PUBLIC ACCOUNTANT - Polar Falcón, Ernesto Augusto (2011)
This article shows one of the studies made in the first objective of the Research Study 2011, which is taking place within the schedule established. There is concern that the dissemination of concepts and proposals for Intellectual Capital, has been profuse, based on advances in knowledge management and the commitment to implement the Management and Training Knowledge Networks. Therefore, we reviewed the content of articles published by faculty researchers and teachers in the magazine QUIPUKAMAYOC guests since 2001, having found interesting articles whose titles are noted in our dogs to locate and read its contents to start a process study on these important issues. On the other hand, the research reached the material was delivered to participants at the XII General Assembly of ALALFEC, Knowledge Management and Management and Training Knowledge Networks. Reprints expressive received titles contain important areas of study that should be considered as the starting material as possible to understand concepts and proposals as well as general approaches to action. It has tried to present those paragraphs that give us further explanation of Intellectual Capital, but we feel we need to have elements of greater depth and scope to achieve a comprehensive understanding and reaching for the Specialist degree in these subjects. Teachers and students have a great challenge to break into these issues and apply innovative studies for the formation of Certified Public Accountant in Peru. Do not forget that in future international events we attend, these issues take precedence and is required to be prepared to actively participate and demonstrate that even in our country and we are up to date on these issues and we are applying the teaching and learning that we apply to the Faculty . Which is why, to raise final conclusions of the article pointed out ways to promote positive actions that lead to better preparation in these areas and excellent applications to reach the corporate objectives in the Faculty and the recognition of our contributions ALAFEC academic and professional at its next General Assembly. We call upon reading the article and intellectual support requested.